Drying behavior and consumer acceptance of oven dried chili (Capsicum frutescens L. Cv. Labuyo) leaves - Tadios, Gia Marie T.
ABSTRACT The drying behavior and consumer acceptance of oven dried chili leaves were investigated. In addition, the effects of drying temperature on the drying time, drying rate and dried product quality in terms of color and chlorophyll retention was evaluated. Chili leaves (Capsicum frutescens L. Cv. Labuyo) were dried at temperatures of 40, 50 and 60°C using a household electric oven. The data obtained from the drying tests were used in drawing the drying curves. The effects of drying temperature on the color quality and consumer acceptance of chili leaves were determined. The amount of chlorophyll retained in all dried chili leaves were computed on the basis of the chlorophyll content of fresh leaves. The drying curves of chili leaves showed constant and falling rate periods for oven drying at 40 and 50°C, and a falling rate period alone for oven drying at 60°C. Increase in the drying temperature increased moisture removal and drying rate of chili leaves, and shortened the drying time considerably. The changes in the color and chlorophyll retention of chili leaves after drying were dependent on the drying temperature. Oven dried chili leaves were significantly (p < 0.05) darker and less green than fresh leaves. The sensory scores for appearance, color, aroma, herb flavor and overall acceptance of oven dried chili leaves significantly (p < 0.05) increased as the drying temperature increased. The study showed that the temperature of drying influenced the drying behavior, product quality and consumer acceptance of oven dried chili leaves. Data revealed that an increase in oven temperature when drying chili leaves resulted to increased drying rate and shortened drying time. Oven drying of chili leaves at 60°C is recommended for least quality changes and greater consumer acceptance.